EARLY SEX EDUCATION FOR ELEMENTARY SCHOOL STUDENTS - wirdiana Zuraida (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
The purpose of this study is to reveal about early sex lessons for elementary school students. Through a descriptive qualitative research method that explains in detail and completely about a phenomenon that is currently occurring. Early Sex Education for Elementary School Students is an effort to provide children with an understanding of their bodies, the changes they will experience, and how to protect themselves from potential dangers in a way that is appropriate for their age and developmental level. Early Sex Education refers to teaching children basic knowledge about their bodies, understanding physical and emotional changes, and how to protect themselves from potential harm. This education is provided in an age- and developmentally appropriate manner, with a focus on topics such as bodily autonomy, privacy, and respectful interactions. Sex Education for Students is an essential aspect of their holistic development, designed to provide age-appropriate knowledge about human anatomy, reproduction, emotional changes, relationships, and personal safety. It empowers students to make informed decisions, respect others, and understand their own growth